Arbutus bicolor (Ericaceae, Arbuteae), a new species from Mexico - González-Elizondo, M. Socorro; González-Elizondo, Martha; Sørensen, Paul D. (Instituto de Ecología, A.C., 2012)
Arbutus bicolor S. González, M. González et P. D. Sørensen, sp. nov. is described and illustrated. It is related to A. xalapensis H.B.K. and has been generally misidentified as A. glandulosa M. Martens & Galeotti, a synonym of the latter name. The new species is distinguished by having densely glandular pubescent branchlets and petioles; markedly bicolored leaves that are whitish to pale ochroleucous below due to a dense and uniform indument of tightly curled hairs, leaves red at senescence; and pink, rarely white flowers. Arbutus bicolor is widely distributed in the Sierra Madre Occidental and the Transvolcanic Belt and reaches the western slopes of the Sierra Madre Oriental in central Mexico. Sporadic hybridization occurs with A. madrensis S. González, A. occidentalis McVaugh & Rosatti, A. tessellata Sørensen, and A. xalapensis. A key to distinguish A. bicolor from other Mexican tree species of Arbutus is provided.